Microsoft SharePoint Building Office 2007 Solutions in C# 2005 - Hillier, Scot P. (Apress : Imprint: Apress, 2007)
Microsoft SharePoint: Building Office 2007 Solutions in C# 2005 is the third edition of Scot Hilliers market-leading SharePoint book. This book features extensive updates to the previous edition, with a complete focus on SharePoint 2007 and its integration with the 2007 Microsoft Office System. It also features new approaches for using SharePoint to improve business efficiency as well as new workflow solutions for SharePoint and BizTalk, plus a new chapter on building a SharePoint solution from start to finish. With this book, you'll gain intermediate-level guidance for designing and deploying business solutions based on Microsoft SharePoint 2007 technologies. Hillier defines the business cases and scenarios for these technologies. He also reviews the installation, configuration, and administration of business solutions based on Microsoft SharePoint technologies, and provides programming instruction, guidance, and examples for custom web parts and solutions.